Effectiveness of 18-hour lactation management course organised by district health office for health staff - Tan, Kok Leong; Ghani, S.N. (Faculty of Medicine, University of Malaya, 2007)
This was a cross-sectional study which attempts to assess the effectiveness of the 18-hour lactation management course organised by Klang District Health Office for its health staff. The course was conducted for three days from 19 to 21 September, 2006 with a total of 18 hours, comprising 15 hours of lectures and three hours of supervised clinical experience. There were a total of 46 participants for the course. The pre- and post-test scores of the participants from the course were used for analysis. This study showed that the mean pre-test versus mean post-test scores were 12.63 and 19.87. The difference in the mean score was statistically significant (p < 0.001, 95%CI -8.285, -6.193). The difference was significant for the staff nurse, community nurse and assistant nurse but not for doctors. In conclusion, the 18-hour duration lactation management course was effective at improving the knowledge and skills on breastfeeding management for the health staff.